The Effects of Clinical Nursing Practice Guideline Implementation in Patients with Colorectal Cancer Receiving Stoma Creation on Quality of Life and Clinical Outcomes - Ladasoontorn, Sujinda; Chaiviboontham, Suchira; Suwanthanma, Weerapat (Nursing Research and Innovation Journal, 2023)
This quasi-experimental research aimed to develop and examine the effects of implementing clinical nursing practice guidelines (CNPG) in patients with colorectal cancer receiving stoma creation on the quality of life and clinical outcomes. Orem’s self-care theory was used as the conceptual framework. The sample consisted of 54 patients with colorectal cancer receiving stoma creation at a university hospital. The patients were divided into two groups: the control group receiving usual care and the experimental group receiving the CNPG implementation, with 27 participants in each group. The CNPG included nursing care at the preoperative, postoperative, and postdischarge phases. Data were analyzed using descriptive statistics, the Chi-square test,the Mann-Whitney U test, and one-way repeated measures analysis of variance. Results showed that the stoma QOL in the CNPG group one month after discharge was significantly higher than before and one week after discharge. For clinical outcomes, the length of stay, postoperative length of stay, postoperative complications, ostomy complications, and 30 days re-admission between the groups were not significantly different. The study revealed that CNPG implementation helps patients have a good quality of life. The incidence of postoperative and ostomy complications in the CNPG group tended to decline. However, further study should be done before fully implementing the CNPG in patients with colorectal cancer receiving stoma creation. Keywords: Clinical nursing practice guideline, Clinical outcomes, Colorectal cancer,Quality of life, Stoma creation